Immune Responses of Piglets Immunized by a Recombinant Plasmid Containing Porcine Circovirus Type 2 and Porcine Interleukin-18 Genes - Chen, Guang-Lei (Viral Immunol, 2014)
In this study, two recombinant plasmids containing the ORF2 gene of porcine circovirus type 2 (PCV2) with or without porcine interleukin-18 (IL-18) were constructed and evaluated for their ability to protect piglets against PCV2 challenge. Transient expression of the plasmids in PK-15 cells could be detected using Western blot. Piglets were given two intramuscular immunizations 3 weeks apart and were challenged with a virulent Wuzhi strain of PCV2 at 42 days after the initial immunization. All animals vaccinated with pBudCE4.1-ORF2 or with pBudCE4.1-ORF2/IL18 developed PCV2-specific antibody and T-lymphocyte proliferative responses. The levels of T-lymphocyte proliferation in piglets immunized with pBudCE4.1-ORF2/IL18 were significantly higher than in those immunized with pBudCE4.1-ORF2, and pBudCE4.1-ORF2/IL18 stimulated a significantly increased production of IFN-γ and IL-2. Furthermore, PCV2 challenge experiments showed that the DNA vaccine-immunized groups can partially prevent PCV2 viremia and significantly reduce the amount of PCV2 virus in the lymphoid tissues, and the piglets immunized by pBudCE4.1-ORF2/IL18 exhibit a marked inhibition of PCV2 replication compared to the pBudCE4.1-ORF2 group. These data demonstrate that the plasmid pBudCE4.1-ORF2/IL18 may be an effective approach for increasing PCV2 DNA vaccine immunogenicity.